TAKINGPOINT : A NAVY SEAL'S 10 FAIL-SAFE PRINCIPLES FOR LEADING THROUGH CHANGE - Gleeson, Brent
Decorated Navy SEAL and successful businessman Brent Gleeson shares his revolutionary approach to navigating and leading change in the workplace